Patterned membranes for improving hydrodynamic properties and mitigating membrane fouling in water treatment: A review. (1st June 2023) - Wang, Qiao; Lin, Weichen; Chou, Shuren; Dai, Pan; Huang, Xia
Highlights: A comprehensive review focuses on patterned membranes' properties and performances. Diversified configurations can be fabricated onto membrane surfaces. Hydrodynamic properties altered by patterns are significant for fouling suppression. Patterned membranes can mitigate different types of fouling in water treatment. Further research is required for patterned membranes' widespread application. Abstract: Membrane technologies have been widely applied in water treatment over the past few decades. However, membrane fouling remains a hinderance for the widespread use of membrane processes because it decreases effluent quality and increases operating costs. To mitigate membrane fouling, researchers have been exploring effective anti-fouling strategies. Recently, patterned membranes are gaining attention as a novel non-chemical membrane modification for membrane fouling control. In this paper, we review the research on patterned membranes used in water treatment over the past 20 years. In general, patterned membranes show superior anti-fouling performances, which mainly results from two aspects: hydrodynamic effects and interaction effects. Due to the introduction of diversified topographies onto the membrane surface, patterned membranes yield dramatic improvements on hydrodynamic properties, e.g., shear stress, velocity field and local turbulence, restraining concentration polarization and foulants' deposition on the membrane surface. Besides, the membrane-foulant and foulant-foulant interactions play an important role in the mitigation of membrane fouling. Due to the existence of surface patterns, the hydrodynamic boundary layer is destroyed and the interaction force as well as the contact area between foulants and surface are decreased, which contributes to the fouling suppression. However, there are still some limitations in the research and application of patterned membranes. Future research is suggested to focus on the development of patterned membranes appropriate for different water treatment scenarios, the insights into the interaction forces affected by surface patterns, and the pilot-scale and long-term studies to verify the anti-fouling performances of patterned membranes in practical applications. Graphical abstract: Image, graphical abstract